2012
DOI: 10.5861/ijrset.2012.98
|View full text |Cite
|
Sign up to set email alerts
|

Nature of classroom environment and achievement in integrated science: A test of efficacy of a constructivist instructional strategy

Abstract: Results of several studies on the relationship between science students' perceptions of their classroom environments and their cognitive and affective achievements indicate strong association between the perceptions and the achievements. While this underscores the need for more effective relations in the classrooms, the issue of the effectiveness of some contemporary instructional strategies for teaching science in different classroom environments has not been addressed. This study, therefore, sought to find o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
2
4
1
3
Order By: Relevance
“…The experimental group taught using this pedagogy did not show any superior performance in the cognitive dimension than their counter parts taught through expository method [F (1,97) =2.68, p>0.05], as reported in Table III. This is in accord with the findings of previous studies (Chang, 2000;Chang & Bell, 2002;Igwebuike & Oriaifo, 2009) but presents a stark contrast to findings in studies by Zietsman and Hewson (1986), Trumper (1990Trumper ( , 1991; Asim (1998); Bajah and Asim (2002);Ndioho (2007).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The experimental group taught using this pedagogy did not show any superior performance in the cognitive dimension than their counter parts taught through expository method [F (1,97) =2.68, p>0.05], as reported in Table III. This is in accord with the findings of previous studies (Chang, 2000;Chang & Bell, 2002;Igwebuike & Oriaifo, 2009) but presents a stark contrast to findings in studies by Zietsman and Hewson (1986), Trumper (1990Trumper ( , 1991; Asim (1998); Bajah and Asim (2002);Ndioho (2007).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, Ndioho's (2007) study indicated that conceptual change pedagogy was significantly more effective in teaching genetics to secondary school biology students than conventional lecture method. Studies by Chang (2000), Chang and Bell (2002), and Igwebuike and Oriaifo (2009), in the area of cognitive achievement, present some contradictions to the result of this study but support the present study in the area of affective achievement. Specifically, Chang (2000) and Chang and Bell (2002) found that this instructional strategy improved students' perceptions of interest, satisfaction, enjoyment and achievement, willingness to attend, listen to lesson and participate in discussion; and increased learning commitment out of class.…”
Section: International Journal Of Research Studies In Educational Teccontrasting
confidence: 59%
See 2 more Smart Citations
“…preguntas que se planteaban en ese entonces desde la pedagogía. En este mismo orden de ideas, surgió la llamada pedagogía conceptual, la cual se enfoca en la enseñanza para la adquisición de competencias para que los estudiantes logren empoderarse de forma positiva de sus procesos de aprendizaje (Igwebuike y Oriaifo, 2012). Con base en lo expuesto, la evolución de perspectivas teóricas sobre la pedagogía y las estrategias que se utilizan para su desarrollo, están siendo transformadas por la incorporación de la tecnología en los procesos de enseñanza (Ali et al, 2013).…”
Section: Estrategias Pedagógicasunclassified